Composite materials - Society of Manufacturing Engineers ([Dearborn, Mich.] : Society of Manufacturing Engineers, 2005)
Features a detailed explanation of the important mechanical properties of thermoset fiber-reinforced composites. The primary types of reinforcement materials: glass, carbon and aramid are examined, as well as the major matrix materials: polyester, epoxy, bismaleimide, and polyimide. The use of thermoplastic composite materials is also highlighted
Executive producer, Steven R. Bollinger ; producer/director/cameraman, Jerome T. Cook ; written by John A. Vaccari
DVD format
Keywords: Fibrous composites; Composite materials